2023
DOI: 10.1155/2023/8886503
|View full text |Cite
|
Sign up to set email alerts
|

Study on Optimal Extraction and Hypoglycemic Effect of Quercetin

Lei Zhang,
Ming-yue Pan,
Tao Li
et al.

Abstract: Quercetin was extracted from Portulaca oleracea L. through biphasic acid hydrolysis to investigate its potential as a suppressor of dipeptidyl peptidase IV (DPP-IV) and its hypoglycemic effect in type 2 diabetic mice. The extraction procedure was optimized utilizing the response surface method (RSM) in a single-factor experimental setting. An extraction efficiency of 0.675% was achieved using the following optimized parameters: 0.064 mol/L vitriol, 1 : 109.155 solid-liquid ratio, and 21.408 min ultrasonication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…The results of molecular docking showed that nine active components had good binding ability with key protein INSR, including Ginkgolic acid (GA13:1), Ginkgolic acid (GA15:1), Gypenoside XXVII, Gypenoside XXVIII, Hesperetin, Nicotiflorin, Quercetin, Spinasterol and Gypenoside XVII. Recent studies show that hesperidin, quercetin and spinach sterol all have obvious therapeutic effects on diabetes [ 43 , 44 , 45 ], which further verifies the accuracy of screening active compounds by network pharmacology and molecular docking. In particular, we found that Gypenoside XVII could bind to six core proteins strongly, and the docking scores were high among the screened compounds.…”
Section: Discussionmentioning
confidence: 90%
“…The results of molecular docking showed that nine active components had good binding ability with key protein INSR, including Ginkgolic acid (GA13:1), Ginkgolic acid (GA15:1), Gypenoside XXVII, Gypenoside XXVIII, Hesperetin, Nicotiflorin, Quercetin, Spinasterol and Gypenoside XVII. Recent studies show that hesperidin, quercetin and spinach sterol all have obvious therapeutic effects on diabetes [ 43 , 44 , 45 ], which further verifies the accuracy of screening active compounds by network pharmacology and molecular docking. In particular, we found that Gypenoside XVII could bind to six core proteins strongly, and the docking scores were high among the screened compounds.…”
Section: Discussionmentioning
confidence: 90%